Collision avoidance of satellites using ionospheric drag. (September 2022) - Kleinig, Thomas; Smith, Brenton; Capon, Christopher
Abstract: 50, 000+ satellites are scheduled for launch by 2030, bringing both massive opportunities and equally massive challenges. Key among these challenges is the ability to sustainably operate Low Earth Orbit (LEO) spacecraft in an increasingly congested environment where collision avoidance manoeuvres are routine and fuel is limited. This paper explores the application of ionospheric drag as an alternative, propellantless collision avoidance mechanism for satellites with altitudes ranging between 350 and 500 km. This is achieved through the use of an in-house propagation suite developed to support UNSW Canberra Space's in-orbit Ionospheric Aerodynamic Experiment (IEX) on the M2 spacecraft (NORAD ID: 47967 & 45727). The relative impact of neutral (thermospheric) to charged (ionospheric) drag on along-track separation for a range of spherical bodies with surface potentials ranging between 0 V to -100 V with respect to a quasi-neutral freestream plasma was investigated. This provides a first-order indication of the potential effectiveness of ionospheric drag for collision avoidance based on prior numerical and ground-based investigations into ionospheric drag. The Debris Risk Assessment and Mitigation Analysis software from the European Space Agency was also harnessed to discern the relative performance of both the charged and flared attitude satellites against a common control satellite. The ESA stipulates that a Collision Probability Level value greater than the accepted value of 1 E − 04 between two satellites requires a risk avoidance manoeuvre, with a conservative approach requiring manoeuvres for values greater than 1 E − 05 . For all test regimes at 350 k m altitude, at least a 60% reduction in time to achieve the NASA approved risk reduction factor of 31.6 at the time of closest approach for a pre-manoeuvre Collision Probability Level of 2 . 8 E − 05 was achieved when using the flared neutral method in comparison to the feathered charged method. Based on these results, this paper finds that ionospheric drag may represent a useful alternative propellantless collision avoidance mechanism for satellites within the altitude range of 350 to 500 km. Future work is needed to refine ionospheric drag models and consider the absolute effectiveness of using ionospheric drag at higher altitudes and in tandem applications to the flared arrangement. Highlights: Ionospheric drag can successfully manoeuvre satellites to avoid collisions. Ionospheric drag is inferior to industry standard avoidance manoeuvres. High Low Earth Orbit altitudes show ionospheric drag becomes more competitive. The adopted python approach provides flexibility for future satellite simulations.